Impact of Stress Hyperglycemia on Early Neurological Deterioration in Acute Ischemic Stroke Patients Treated With Intravenous Thrombolysis - Wang, Ling; Cheng, Qiantao; Hu, Ting; Wang, Nuo; Wei, Xiu'e; Wu, Tao; Bi, Xiaoying (Frontiers in Neurology, 2022)
Background and purpose: The poor prognostic effect of stress hyperglycemia on acute ischemic stroke patients (AIS) has been widely reported. However, its predictive value of early neurological deterioration (END) after intravenous recombinant tissue-type plasminogen activator (IV-rtPA) in AIS patients is still unclear. This study aim to evaluate the impact of stress hyperglycemia on the risk of END after IV-rtPA. Methods: A total of 798 consecutive patients treated with IV-rtPA were included in this study. Stress hyperglycemia ratio was calculated as random admission glycemia/glycosylated hemoglobin (HbAlc). END was defined as National Institutes of Health Stroke Scale Score (NIHSS)≥4 points with 24 hours after IV-rtPA. Patients with prior history of diabetes or HbAlc≥6.5% were considered to have diabetes mellitus. Patients were tertiled according to the SHR value. Multivariate logistical regression was used to evaluated the risk of END between SHR categories. Results: Totally, 139 (17.4%) patients had END. After adjusted confounders, compared with the lowest tertile group, the highest tertile group had a high risk of END (OR, 1.95; 95% CI, 1.21-3.15; P=0.006), the predictive value of high SHR on END is still significant in patients with diabetes mellitus (OR, 3.05; 95% CI, 1.29-7.21; P=0.011). Conclusion: Higher SHR identified patients with severe stress hyperglycemia can be used to predict higher risk of END after IV-rtPA.